The perception of the administrative management in the pension 65 program, Huánuco 2019 - Fano-Celis, Evelyn M. (2020)
The objective of this research was the perception of administrative management by the workers of the Pensión 65 program, Huánuco 2019. Methods: The study was quantitative in focus, with a descriptive, non-experimental, cross-sectional and prospective design. The sample consisted of 120 workers from Pension 65. In data collection, an interview with general characteristics and a questionnaire to measure the administrative management of the Pension 65 program, previously validated and reliable, were applied. And ethical considerations were applied to the research. The results showed that 74 % (62) were male and 46 % (38) female. Regarding age, 34 % (50) were between 21-30, 25.9% (38) were between 31-40, 22.4 % (33) were 41-50 and 17.7 % (26) were older than 51 It is concluded that the level of perception of the workers about the planning of administrative management, 35% (42) had an adequate level, 38 % (46) an acceptable level and 27 % (32) an inadequate level. Regarding the level of perception about the direction, 57 % (68) had an acceptable level, 23% (28) had an adequate level and 20 % (24) inadequate. Regarding the level of perception about the control, 47 % (56) had an acceptable level, 25 % (30) adequate level and 28% (34) inadequate level.